2005
DOI: 10.1016/s1808-8694(15)31304-5
|View full text |Cite
|
Sign up to set email alerts
|

Breathing mode influence in craniofacial development

Abstract: We concluded that mouth breathing children tend to have higher mandibular inclination and more vertical growth. These findings support the influence of the breathing mode in craniofacial development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 28 publications
5
47
0
12
Order By: Relevance
“…But in deciduous dentition the facial dimensions did not correlate with muscle strength, corroborating the fact that masticatory muscle function and facial form interaction can occur later. 4,8,24 This study did not find association between facial morphology and malocclusion in deciduous dentition, agreeing with the findings of Katz et al 7 (2004). However, in the early mixed dentition, children with a higher AFH/FWB ratio were significantly more likely to have crossbite (Table 2).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…But in deciduous dentition the facial dimensions did not correlate with muscle strength, corroborating the fact that masticatory muscle function and facial form interaction can occur later. 4,8,24 This study did not find association between facial morphology and malocclusion in deciduous dentition, agreeing with the findings of Katz et al 7 (2004). However, in the early mixed dentition, children with a higher AFH/FWB ratio were significantly more likely to have crossbite (Table 2).…”
supporting
confidence: 91%
“…Past studies showed asymmetry in masticatory muscle activity and thickness, 1 decrease in bite force magnitude, a smaller number of teeth in contact, 2 and asymmetric jaw motion and growth of the orofacial structures [3][4][5][6] in children with crossbite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the literature is in disagreement showing higher rates (66.3% and 77.7%) 28,7 , as well as lower ones (5% to 30%) [29][30][31][32][33] . These differences can be explained by the methodologies used in other investigations, especially in regards of the diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 However, these clinical signs have been queried, since not all individuals who presented them were predominantly mouth breathers, and this facial type could also be a congenital trait, not necessarily related to the breathing mode. 5,6 Muscle patterns and skeletal growth are influenced only slightly by the breathing mode, since they are genetically transmitted and the facial type could be a congenital trait. 7 Proffit and Fields 8 (2000) have also emphasized the strong correlation between breathing mode and craniofacial dimensions.…”
Section: Introductionmentioning
confidence: 99%